Antimicrobial Stewardship and Clostridium difficile–Associated Diarrhea. (October 2013) - Piacenti, Frank J.; Leuthner, Kimberly D.
Antimicrobial stewardship programs are essential to health care institutions to promote the appropriate use of antibiotics not only to decrease antimicrobial resistance but to prevent the spread and infection of Clostridium difficile. Clostridium difficile –associated diarrhea is increasing rapidly in the United States and is now considered a major public health problem that poses an immediate threat to the health of patients prescribed antibiotics, more so than antimicrobial resistance. Clostridium difficile –associated disease is the result of collateral damage to the normal bacterial flora of the human body, which is an inevitable consequence of any antibiotic use. Antimicrobial stewardship programs such as audit with feedback and antibiotic restriction are designed to help limit Clostridium difficile infections and other hospital-associated organisms by optimizing antimicrobial selection, dosing, de-escalation, and duration of therapy. These programs also incorporate implementation of hospital-wide guidelines, staff education, enforcement of infection-control policies, and the use of electronic medical records when possible to help control antibiotic use. This article reviews the literature on how antimicrobial stewardship programs impact Clostridium difficile rates and discusses experiences in designing, implementing, monitoring, and follow-through of such programs.